Le cadrage politique et l’ethos de Justin Trudeau sur Instagram : un storytelling héroïque entre émotion et celebrity politics - Kelly Céleste Vossen (Communiquer, 2019)
In the light of the growing presence of political actors on Instagram, it seems essential to tackle the use of the platform by political leaders. This article explores the way in which communication advisors have framed the ethos of Justin Trudeau on Instagram during its campaign and through the first 100 days of its government. With that purpose in mind, we have adopted a largely quantitative approach, supported by a discourse analysis. The results shed the light on an ethos based on authenticity, compassion and competence. Justin Trudeau is presented thanks to strategies based on pathos and celebrity politics, through a heroic and positive storytelling.